2012
DOI: 10.1177/0194599812464193
|View full text |Cite
|
Sign up to set email alerts
|

A Meta‐analysis of Voice Outcome Comparing Calcium Hydroxylapatite Injection Laryngoplasty to Silicone Thyroplasty

Abstract: Injection laryngoplasty with CaHA and MT with silicone appear to achieve comparable voice improvement within 1 year, but a definitive conclusion is limited by a lack of standardized outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 41 publications
4
27
0
5
Order By: Relevance
“…In populations with GI, previous studies found that IL resulted in improved voice‐related quality‐of‐life measures such as the Voice Handicap Index‐10 (VHI‐10) and Voice Performance Questionnaire . The procedure has been shown to reduce severity of hoarseness, breathiness, and strain, as measured using the grade, roughness, breathiness, asthenia, and strain and Consensus Auditory‐Perceptual Evaluation of Voice (CAPE‐V) perceptual scales in patients with GI secondary to vocal fold paralysis and bowing .…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…In populations with GI, previous studies found that IL resulted in improved voice‐related quality‐of‐life measures such as the Voice Handicap Index‐10 (VHI‐10) and Voice Performance Questionnaire . The procedure has been shown to reduce severity of hoarseness, breathiness, and strain, as measured using the grade, roughness, breathiness, asthenia, and strain and Consensus Auditory‐Perceptual Evaluation of Voice (CAPE‐V) perceptual scales in patients with GI secondary to vocal fold paralysis and bowing .…”
Section: Introductionsupporting
confidence: 86%
“…30 In populations with GI, previous studies found that IL resulted in improved voice-related quality-of-life measures such as the Voice Handicap Index-10 (VHI-10) and Voice Performance Questionnaire. [32][33][34] The procedure has been shown to reduce severity of hoarseness, breathiness, and strain, as measured using the grade, roughness, breathiness, asthenia, and strain and Consensus Auditory-Perceptual Evaluation of Voice (CAPE-V) perceptual scales in patients with GI secondary to vocal fold paralysis and bowing. 35 Significant improvement in acoustic voice measures following IL have also been reported, such as reduced Dysphonia Severity Index 36 in patients with GI due to vocal paralysis and presbylaryngis and improved noise-toharmonic ratio in patients with vocal fold bowing, paresis, paralysis, and scarring.…”
Section: Introductionmentioning
confidence: 99%
“…However, the hydroxyapatite has a lifespan on average of 18 months. 19 that are published in the literature. 20,21 Therefore, we believe that technical variability did not have a significant impact on our results.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that, for a similar early (<2 years) effectiveness, IL will offer a cost saving of 596 CA$. However, the hydroxyapatite has a lifespan on average of 18 months . With the MT's results now showing effectivity of at least 5 years, the cost/benefit analysis could switch in favour of MT, especially for patients with a life expectancy of more than 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…With the latter, there is risk of breathing problems as some narrowing of the airway is expected after surgery. Nonrandomized studies looking at injection versus laryngoplasty have shown very similar results in the short‐term and long‐term, although there was a higher rate of revision surgery in the injection group …”
Section: Introductionmentioning
confidence: 83%